1997
DOI: 10.1007/s002590050179
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative parathyroid gland localization with technetium-99m sestamibi in secondary hyperparathyroidism

Abstract: Technetium-99m sestamibi scintigraphy has become a valuable tool in locating parathyroid glands in patients with primary hyperparathyroidism. The aim of this study was to evaluate its usefulness in secondary hyperparathyroidism. Twenty patients were injected intravenously with 740 MBq of 99mTc-sestamibi and images were obtained at 15 min and 2 h post injection. All patients underwent parathyroid ultrasonography (US) as well as bilateral surgical neck exploration and 64 parathyroid glands were removed. US revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
2
8

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 8 publications
1
14
2
8
Order By: Relevance
“…According to previous studies, dual-phase scintigraphy yielded a low sensitivity for hyperplastic glands. 4,6,7,33 However, SPECT did not improve the sensitivity and delayed SPECT even reduced the sensitivity (54% vs. 44%), which may be attributed to the spatial resolution limits of SPECT and the low signal in some glands against background noise. Gallowitsch et al 22 reported lower sensitivity (38%) with dual-phase scintigraphy, but higher sensitivity with SPECT (62%).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…According to previous studies, dual-phase scintigraphy yielded a low sensitivity for hyperplastic glands. 4,6,7,33 However, SPECT did not improve the sensitivity and delayed SPECT even reduced the sensitivity (54% vs. 44%), which may be attributed to the spatial resolution limits of SPECT and the low signal in some glands against background noise. Gallowitsch et al 22 reported lower sensitivity (38%) with dual-phase scintigraphy, but higher sensitivity with SPECT (62%).…”
Section: Discussionmentioning
confidence: 62%
“…3 In multiglandular disease, which is present in about 12% of patients with pHPT and is also found in some patients with secondary (sHPT) or tertiary hyperparathyroidism (tHPT), the sensitivity for both adenomas and hyperplastic glands tends to be much lower (44%-54%). [4][5][6][7] To improve the diagnostic performance of 99m Tc-MIBI, single photon emission computed tomography (SPECT) is sometimes added to routine planar scans. SPECT improves contrast and provides a 3-dimensional visualization.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of imaging procedures in secondary hyperparathyroidism patients has been reported to be lower than in primary hyperparathyroidism because of multiglandular hyperplastic disease rather than solitary adenomas [24]. However, there are also series published showing high sensitivities for 99m Tc-MIBI when compared with other imaging procedures, at least to localize one pathological gland [9][10][11][12]25].…”
Section: Discussionmentioning
confidence: 94%
“…Imaging of the parathyroid glands using 99m Tc-MIBI has been widely used in the identification of solitary parathyroid adenomas, which is the most common finding in patients with primary hyperparathyroidism [7,8]. Some groups indicate that 99m Tc-MIBI imaging can also be used initially to localize abnormal glands in haemodialysis patients with secondary hyperparathyroidism, before ultrasound, magnetic resonance and computed tomography in preoperative parathyroidectomy patients [9][10][11][12][13]. However, the need for imaging in such patients is still debatable because of the low sensitivity in the detection of hyperplastic multiglandular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Notre étude confirme cette corrélation puisque le diamètre maximal moyen des glandes parathyroïdes était significativement plus élevé dans le groupe des glandes positives en scintigraphie ou en échographie. Certains auteurs ont établi une corrélation entre le volume de la glande et sa détection isotopique sans pouvoir montrer une corrélation similaire avec le poids [15,16]. Dans notre expérience, une telle corrélation a pu être mise en évidence, pour l'échographie comme pour la scintigraphie, probablement du fait de la plus grande taille de notre échantillon.…”
Section: Discussionunclassified